RESEARCH ON FORCE ANALYSIS AND DETECTION OF QUASI-RECTANGULAR SHIELD MACHINE’S CUTTER HEADS - WU EnQi; HOU TianFan; MIN Rui; LIU GaoHong; WANG XiaoHui (Jixie qiangdu)
The quasi-rectangular shield machine adopts the combined cutting form of two large circular spoke type cutter heads and two eccentric cutter heads whose force state is relatively complex. In order to investigate the thrust fluctuation of each cutter head,an in-situ detection method based on finite element analysis was proposed. Firstly,the calculation models of thrust and torque of cutter heads were established. By using the finite element analysis method,the relationship between the thrust of cutter heads and the stress of the detection points on the chest plate was obtained. By using the collected stress system,the realtime stress status of each detection point under the construction process was obtained. And then the actual thrust of the cutter heads and the thrust distribution of each cutter head were also derived by comparing the stress status with the simulation results.The experiment result shows that this method can measure the thrust of each cutter head in real-time,which provides theoretical guidance and reference for the structure design and safe operation.